Empirical investigation of the impact of using co-design methods when generating proposals for sustainable travel solutions. Issue 4 (1st October 2016) - Mitchell, Val; Ross, Tracy; May, Andrew; Sims, Ruth; Parker, Christopher
Abstract: This paper presents an empirical comparison of idea generation within the context of reducing the number of single occupancy car journeys to and from a UK university campus. Separate co-design and consultative groups were matched with respect to (1) creativity when problem solving, (2) normal commuting mode and (3) intention to adopt sustainable behaviours. The co-design group generated a significantly greater number of innovative ideas than the consultative group (using an email-based methodology); however, this was due to the greater number of total ideas (rather than the higher proportion of innovative ideas) generated by this group. The co-design group was able to think more systemically about potential solutions and generate proposals that were not either linked to their own commute mode, or aligned with any one specific mode of transport. The findings suggest that co-design offers benefits as a process for idea generation within the sustainable travel context as it promotes idea generation and a more holistic perspective on the problem and potential solutions.